1996
DOI: 10.1021/jp952831a
|View full text |Cite
|
Sign up to set email alerts
|

Association of Electroactive Counterions with Polyelectrolytes. 6. Electrostatic and Coordinative Binding of Ru3+/2+ Centers to a Copolymer of Acrylic Acid and Acrylonitrile

Abstract: A random copolymer of acrylic acid and acrylonitrile was prepared in which the functionality on the polymer chain consisted of 93% carboxylic acid groups, 4.1% nitrile groups, and 2.9% acid anhydride groups. The nitrile groups were used to coordinate Ru(NH 3 ) 5 2+ centers to the copolymer. The anionic carboxylate groups produced at pH values above ∼3.5 were used to bind Ru(NH 3 ) 6 3+ counterions to the resulting polyanionic copolymer. The electrochemical oxidation or reduction of the two redox centers bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5] For example, Yoshikawa et al reported that a polyelectrolyte membrane made with polyacrylic acid and poly(4-vinylpyridine) showed electrostatic binding of electroactive counterions. 6,7 These materials are usually prone to the effects of the external environment, resulting in change in charge density and thereby altering wettability, permeability towards ions, and stiffness of films. [8][9][10][11][12][13][14] Potential applications of such ''smart'' membranes include gates to control the permeability in microfluidic devices, surface coatings in chromatographic separations and controlled release systems, and artificial muscles to drive mechanical motion.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] For example, Yoshikawa et al reported that a polyelectrolyte membrane made with polyacrylic acid and poly(4-vinylpyridine) showed electrostatic binding of electroactive counterions. 6,7 These materials are usually prone to the effects of the external environment, resulting in change in charge density and thereby altering wettability, permeability towards ions, and stiffness of films. [8][9][10][11][12][13][14] Potential applications of such ''smart'' membranes include gates to control the permeability in microfluidic devices, surface coatings in chromatographic separations and controlled release systems, and artificial muscles to drive mechanical motion.…”
mentioning
confidence: 99%
“…The prolonged motion of the gel on the water surface is chemically driven and it is different from the motion observed in an oil/water system where repetitive changes in the interfacial tension at oil−water interface causes a self-movement of the oil drop. , The driving force of the present case is the surface spreading of the organic solvent released from the gel.…”
Section: Introductionmentioning
confidence: 65%
“…Relatively simple electrochemical techniques offer convenient means for estimating diffusion coefficients of electroactive molecules With concentrations of the polyelectrolyte sufficient to cause essentially all of the multiply charged electroactive counterions to bind to the polyelectrolyte, the electrochemically evaluated diffusion coefficients of the counterions were assumed to match that of the polyelectrolyte. Although considerable circumstantial evidence in support of this assumption has been obtained, it remained an assumption.…”
mentioning
confidence: 99%